การกำจัดตะกั่วและทองแดงจากน้ำเสีย โดยซิลิกาเจลที่ใช้แล้วเคลือบด้วยเหล็กออกไซด์ - เบญจวรรณ วงศ์ศิริ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
An iron-oxide coated waste silica gel was prepared for using as an adsorbent. Two preparation methods, modified adsorption method and modified precipitation method, were used. For the modified adsorption method, 5 grams of silica gel pretreated at 100 ํC for 24 hours were mixed with 10 mL of 0.35 %w/v iron concentration at pH 12.0. For the modified precipitation method, 5 grams of silica gel pretreated at 500 ํC for 3 hours were mixed with 25 mL of 0.25 %w/v iron concentration before adjusting the pH to 7.0. The obtained silica gel was baked at 80 ํC for 10 hours and further calcined at 550 ํC for 6 hours. The coated silica gels showed higher metals adsorption capacity than the uncoated one. In the study of metal removal using the adsorbent, the effect of contact time and pH of solution were investigated. The contact time of 30 minutes was used in adsorption experiments. Pb and Cu could be adsorbed on the adsorbent at pH 5.5. The maximum adsorption capacity of Pb and Cu are 11.82 and 3.55 mg/g silica gel, respectively. When the pH of metal solution is 3 or lower, the solubilization of iron oxide coated on surface of silica gel is observed. The presence of NaCl in metal solution in the level of 0.01 M or higher reduces the adsorption capacity of Pb and Cu. The adsorption isotherm of Pb and Cu are defined by the function of Freundlich. The adsorbents prepared from waste silica gel of different sources have adsorption capacity in the range of 8.21 11.82 and 2.12 3.55 mg/g silica gel for Pb and Cu, respectively. The maximum %removal of Pb and Cu from real wastewater having initial concentration of 22.66 mg/L for Pb and 13.11 mg/L for Cu are 89.48 % and 83.52%, respectively